Autocorrelation of the Ground Vibrations Recorded by the SEIS‐InSight Seismometer on Mars. Issue 4 (30th March 2021) - Compaire, N.; Margerin, L.; Garcia, R. F.; Pinot, B.; Calvet, M.; Orhand‐Mainsant, G.; Kim, D.; Lekic, V.; Tauzin, B.; Schimmel, M.; Stutzmann, E.; Knapmeyer‐Endrun, B.; et al.
Abstract: Since early February 2019, the SEIS (Seismic Experiment for Interior Structure) seismometer deployed at the surface of Mars in the framework of the InSight mission has been continuously recording the ground motion at Elysium Planitia. In this study, we take advantage of this exceptional data set to put constraints on the crustal properties of Mars using seismic interferometry (SI). To carry out this task, we first examine the continuous records from the very broadband seismometer. Several deterministic sources of environmental noise are identified and specific preprocessing strategies are presented to mitigate their influence. Applying the principles of SI to the single‐station configuration of InSight, we compute, for each Sol and each hour of the martian day, the diagonal elements of the time‐domain correlation tensor of random ambient vibrations recorded by SEIS. A similar computation is performed on the diffuse waveforms generated by more than a hundred Marsquakes. A careful signal‐to‐noise ratio analysis and an inter‐comparison between the two datasets suggest that the results from SI are most reliable in a narrow frequency band around 2.4 Hz, where an amplification of both ambient vibrations and seismic events is observed. The average autocorrelation functions (ACFs) contain well identifiable seismic arrivals, that are very consistent between the two datasets. Interpreting the vertical and horizontal ACFs as, respectively, the P‐ and S‐ seismic reflectivity below InSight, we propose a simple stratified velocity model of the crust, which is mostly compatible with previous results from receiver function analysis. Our results are discussed and compared to recent works from the literature. Plain Language Summary: The correlation of seismic records is the basis of seismic interferometry methods. These methods use seismic waves, either from ambient vibrations of the planet or from quakes, that are scattered in the medium in order to recover information about the structure between two seismic sensors. The method is implemented to compute the auto‐correlation functions of the three components of the ground motion recorded by the SEIS seismometer. The comparison of the results obtained from earthquake data to the ones obtained from ambient vibrations demonstrates that the ambient seismic vibration is clearly above the self‐noise of SEIS during early night hours around a specific frequency (2.4 Hz). The seismic vibrations appear to be amplified at this frequency by an unknown mechanism. Some seismic energy arrivals appear consistently in the auto‐correlation functions, at specific propagation times, independent of the data sets and processing parameters tested. These arrivals are interpreted as vertically propagating seismic waves which are reflected on top of crustal layers. Their propagation times can be used to constrain a model of Mars crustal structure. Key Points: Autocorrelation functions (ACFs) of SEIS ambient vibrations and seismic events are computed and validated by intercomparison The stability of autocorrelations at 2.4 Hz resonance favor an excitation by a diffuse seismic wavefield Various arrivals are observed in ACFs and interpreted as seismic reflections on internal discontinuities